2018 IEEE International Symposium on Broadband Multimedia Systems and Broadcasting (BMSB) 2018
DOI: 10.1109/bmsb.2018.8436847
|View full text |Cite
|
Sign up to set email alerts
|

Understanding QoS Applicability in 5G Transport Networks

Abstract: Abstract-5G transport networks will need to accommodate a wide spectrum of services on top of the same physical infrastructure and network slicing is seen as a suitable candidate for providing the necessary quality of service (QoS). Traffic differentiation is usually enforced at the border of the network in order to ensure a proper forwarding of the traffic according to its class through the backbone. With network slicing, the traffic may now traverse many slice edges where the traffic policy needs to be enfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…The particular characterization of the services into categories, such as eMBB or uRLLC, remarks that some parameters can be relaxed or can be seen as less critical from one service respect to the other, even falling on the same service type, an aspect exploited in this work. Some other studies have also revealed this fact when dealing for instance, with the QoS capabilities to be offered by the network [20].…”
Section: Discussionmentioning
confidence: 83%
“…The particular characterization of the services into categories, such as eMBB or uRLLC, remarks that some parameters can be relaxed or can be seen as less critical from one service respect to the other, even falling on the same service type, an aspect exploited in this work. Some other studies have also revealed this fact when dealing for instance, with the QoS capabilities to be offered by the network [20].…”
Section: Discussionmentioning
confidence: 83%
“…For the public network infrastructure, a 5G transport network is assumed based on [6] and [7]. All the RUs present in the use case transmit their traffic up to an access ring composed of several switches connected in a ring fashion.…”
Section: Use Case: Mobile Roboticsmentioning
confidence: 99%
“…Furthermore, the normalized revenues associated to the gold, silver, and bronze graphs are: [5,3,2] for grid monitoring, [4, 2, 1] for bird's eye, and [3, 2, 1] for industrial robotics. The physical infrastructure is composed of six hosts (servers) connected in a two-layer topology reflecting the core network organization used in [15]. For simplicity, we focus on computational capabilities alone and vary the normalized CPU available at each host between 1 and 5.…”
Section: Performance Evaluationmentioning
confidence: 99%